The ecological awareness and luxury consumption - Hahn, Ivanete Schneider; Scherer, Flavia Luciane; Flach, Rosiane Oswald; Back, Larissa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
A recurrent issue is the absence of relationship between ecological awareness and luxury consumption. In this perspective, this study aims to analyze the ecological awareness and propensity to luxury consumption. The research started from a quantitative and descriptive approach, operationalized by a survey with 253 Internet users in the states of Santa Catarina and Rio Grande do Sul - Brazil. Results show that subjects, in general, have a high degree of environmental awareness, showing up, however, somewhat likely to use status. It is inferred that both behaviors are not complementary, and the greater ecological awareness lower propensity to luxury consume.